Exergy analysis of an anaerobic digestion plant fed with dairy cattle waste (Research, Society and Development, 2021)
In order to integrate different processes for the reuse of agricultural waste, the production of biogas and biofertilizer, produced by anaerobic digestion, are essential for the sustainable development and diversification of the Brazilian energy matrix. As the analysis of the thermodynamic performance of these systems is scarce in the literature, this work aimed to associate the physicochemical parameters of dairy cattle residues with the value of their respective chemical exergy. And thus, evaluate the efficiency of the biodigester based on real operational data from Starmilk, located in the municipality of Céu Azul in the west of the State of Paraná, Brazil. The results show that the exergy content of fresh manure was 16.03 MJ/kg, 15.35 MJ/kg for the biofertilizer and 29.55 MJ/m³ (CNTP) of biogas exergy. Based on the analyzes carried out, it is inferred that the analyzed biodigester has an overall exergy efficiency of 72.82%, being able to recover 27.29% of the exergy of cattle manure in the form of biogas.